Bioactive Compounds from Plants - A Short Review - Dayal, Rameshwar (Indian Forester, 2022)
Bryonolic acid; bergenin, hopeaphenol;ursolic acid; agnuside, virdiflorol; labdanyl-3α-ol-18-(3"-methoxy-2"-naphthyl-oate)-3α-L-arabinofuranosyl- (2’-1")-α-L-arabinofuranoside; stipulin and luteolin 4’-rutinoside were isolated and characterized from Tetrameles nudiflora, Vateria indica, Eucalyptus hybrid, Vitex negundo, Peucedanum grande and Dalbergia stipulacea respectively. These pure compounds were found to possess different pharmacological activities.